The use of micro-costing in economic analyses of surgical interventions: A systematic review - Shelley Potter; Charlotte Davies; Gareth Davies; Caoimhe Rice; William Hollingworth (Health Economics Review, 2020)
Background: Compared with conventional top down costing, micro-costing may provide a more accurate method of resource-use assessment in economic analyses of surgical interventions, but little is known about its current use. The aim of this study was to systematically-review the use of micro-costing in surgery. Methods: Comprehensive searches identified complete papers, published in English reporting micro-costing of surgical interventions up to and including 22nd June 2018. Studies were critically appraised using a modified version of the Consensus on Health Economic Criteria (CHEC) Checklist. Study demographics and details of resources identified; methods for measuring and valuing identified resources and any cost-drivers identified in each study were summarised. Results: A total of 85 papers were identified. Included studies were mainly observational comparative studies (n = 42, 49.4%) with few conducted in the context of a randomised trial (n = 5, 5.9%). The majority of studies were single-centre (n = 66, 77.6%) and almost half (n = 40, 47.1%) collected data retrospectively. Only half (n = 46, 54.1%) self-identified as being 'micro-costing' studies. Rationale for the use of micro-costing was most commonly to compare procedures/techniques/processes but over a third were conducted specifically to accurately assess costs and/or identify cost-drivers. The most commonly included resources were personnel costs (n = 76, 89.4%); materials/disposables (n = 76, 89.4%) and operating-room costs (n = 62,72.9%). No single resource was included in all studies. Most studies (n = 72, 84.7%) identified key cost-drivers for their interventions. Conclusions: There is lack of consistency regarding the current use of micro-costing in surgery. Standardising terminology and focusing on identifying and accurately costing key cost-drivers may improve the quality and value of micro-costing in future studies. Trial registration: PROSPERO registration CRD42018099604.
Keywords: 330; Micro-costing; Economic evaluation; Surgery; Systematic review